Ransomware: Evolution, Classification, Attack Phase, Detection and Prevention - Mubarak, Ahmad Sainuri; Insirat, Mutahira Nur; Lutfiya, Muhajira Nurul (Institut Teknologi Adhi Tama Surabaya, 2024)
The modern cybercrime namely ransomware has grown exponentially over the past few years. Ransomware is a type of malware that is the result of sophisticated efforts to infiltrate modern computer systems. Most of these threats are aimed at directly or indirectly making money from victims by demanding a ransom in exchange for a description key. Governments and large corporations are investing heavily to combat cyber threats to their critical infrastructure. Ransomware first appeared in 1980, at that time one had to pay by mail. Ransomware is considered to be malware that has spread widely since 1989 and has caused global financial losses for both individuals and large organizations. Every year losses due to ransomware continue to increase. Therefore, data protection from ransomware is very necessary. Currently, ransomware originators request payment via bitcoin or cryptocurrency. This research provides an overview of ransomware, its evolution, classification, attack phases, detection, prevention, description of research limitations, and finally provides conclusions.